THE ROLE OF LINGUISTIC IMPERIALISM IN GLOBAL ENGLISH DOMINANCE - Sattorova Khumora Bakhshulla kizi (Western European Studies, 2025)
This topic examines the concept of linguistic imperialism, which refers to the dominance of one language over others through political, cultural, and economic means. The analysis explores how English has become the global lingua franca, not merely through organic spread but as a result of deliberate imperialistic strategies tied to colonialism, globalization, and neoliberalism. It discusses how English often overshadows local languages, perpetuating inequalities and reinforcing Western hegemony. The debate includes whether English serves as a tool for empowerment or perpetuates cultural erosion, focusing on the sociopolitical dynamics of language hierarchy and the loss of linguistic diversity
Keywords: linguistic imperialism; global English